Secondary corrosion protection of FeCr(Al) model alloys at 600 °C – The influence of Cr and Al after breakaway corrosion. (15th August 2021) - Eklund, J.; Persdotter, A.; Hanif, I.; Bigdeli, S.; Jonsson, T.
Highlights: The effect of Cr and Al on the secondary corrosion protection after breakaway oxidation of FeCr(Al) alloys has been investigated. Two different behaviours can be distinguished, i.e. formation of fast- or slow-growing Fe-rich oxide scales. Thermodynamic calculations suggest that Cr facilitates the formation of a healing layer, whereas Al reduces the stability of internal oxidation. The slow growth rates may be explained by the ability of an alloy to prevent internal oxidation, enabling the formation of a healing layer. Abstract: The influence of Cr and Al content on the oxidation behaviour of FeCr(Al) model alloys after breakaway oxidation at 600 °C and the underlying mechanisms were investigated in detail with thermogravimetrical analysis (TGA), thermodynamic calculations and advanced electron microscopy. The results showed that a Cr-content of ≥18 wt% drastically reduced the growth rate of the Fe-rich oxide scale, formed after breakaway oxidation, for FeCrAl alloys but not for FeCr alloys. This was attributed to the ability of the Fe(18-25)CrAl alloys to prevent internal oxidation, which enables the formation of a healing layer.